Implementasi Permendiknas No. 24 Tahun 2007 Tentang Standar Sarana dan Prasarana Pada MTs Al-Ihsaniyah dan MTs Aisyiyah 1 Palembang - Indarwan Indarwan (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 1970)
This study aims to determine: 1) The Process of Implementing Permendiknas No. 24 of 2007 concerning Facilities and Infrastructure Standards in Al Ihsaniyah MTs and MTs isy Aisyiyah 1 Palembang, 2) Factors affecting the Implementation of National EducationMinister Regulation No. 24 of 2007 concerning Facilities and Infrastructure Standards in Al Ihsaniyah MTs and MTs isy Aisyiyah 1 Palembang. Data collection techniques used are observation, interviews and documentation. While the analysis technique used inthis study is a qualitative data analysis technique. The results of this study indicate that the educational infrastructure at MTs Al Ihsaniyah Palembang has not met the minimum standard criteria set by the government. Inversely proportional to educational facilities and infrastructure at MTs Aisyiyah 1 Palembang that have met the minimum standard criteria, seen in the observation results that the study room, library, laboratory, leadership room, teacher's room, counseling room, UKS room, warehouse, playground / sports, places of worship, toilets for students and teachers, and other learning resources so that they meet the minimum standards set by the government.